Barotrauma in Technical Diving: An Exploration of Risk Factors and Preventive Measures in Raja Ampat, Southwest Papua, Indonesia - Lusiana Saallo; Erenne Yoseph (Phlox Institute: Indonesian Medical Research Organization, 2025)
Introduction: Technical diving, while offering an unparalleled exploration of underwater environments like Raja Ampat's biodiverse reefs, presents inherent risks, with barotrauma being a major concern. This study aims to analyze barotrauma incidents among technical divers in Raja Ampat, identify risk factors, and propose preventive measures. Methods: A retrospective analysis of barotrauma cases (2018-2023) was conducted in collaboration with local dive centers and medical facilities. Data collected included: demographics, dive profiles, equipment, pre-existing conditions, symptoms, and treatment. Statistical analysis was performed to identify significant associations. Results: A total of 42 barotrauma cases were identified (ear: 69%, sinus: 21%, lung: 10%). Significant risk factors included: rapid ascents (p<0.01), inadequate equalization techniques (p<0.05), and pre-existing conditions like allergies or upper respiratory tract infections (p<0.05). Most cases were mild to moderate and managed with conservative treatment. Conclusion: Barotrauma remains a significant risk in technical diving in Raja Ampat. Strict adherence to safe diving practices, comprehensive pre-dive medical evaluations, and targeted diver education programs are crucial to mitigate these risks.